Komunikasi Humas Bank Indonesia mengenai QRIS melalui Media Sosial Instagram di Kota Ternate - Nurul Sheila Abdullah; Yenni Yuniati (UNISBA Press, 2024)
Abstract. Instagram social media as a communication medium for conveying messages and information in the current era of digitalization is very helpful and makes it easier for every person or institution and organization to carry out the communication process. Through the advantages of social media, every communication process can run and various types of messages can be conveyed instantly without the barriers of time and space. One of them is delivering messages regarding the QRIS service introduced by Bank Indonesia via Instagram social media. As a network of Bank Indonesia's financial and monetary headquarters, the North Maluku Province Representative Office contributes by participating in compiling and publishing a digital money service or Qris. Of the many residents in Ternate City, there are still few people who are aware of technology, especially technology in the field of non-cash services (QRIS). This research uses a qualitative research method with a descriptive case study approach. The researcher considers it important to conduct scientific research in the form of a thesis